ChemInform Abstract: Potassium‐Exchanged Zirconium Hydrogen Phosphate [α‐Zr(KPO4)2]‐Catalyzed Synthesis of 2‐Amino‐4H‐pyran Derivatives under Solvent‐Free Conditions. Issue 40 (September 2016) - Rosati, Ornelio; Pelosi, Azzurra; Temperini, Andrea; Pace, Vittorio; Curini, Massimo
Abstract: The one‐pot three component reaction between dimedone derivatives, malonitrile or cyanoacetate and aryl, alkenyl or alkyl aldehydes provides the title products in generally high yields.